Robust design of LCL filters for single-current-loop-controlled grid-connected power converters with unit PCC voltage feedforward - Li, Xiaoqiang (2019)
The point of common coupling (PCC) voltage feedforward control is widely employed for LCL-type grid-connected converters to prevent large inrush current during startup, reduce steady-state tracking error, and suppress disturbances of grid voltage. Generally, this feedforward loop is ignored in the system modeling and stability analysis for simplicity. However, the grid impedance would be introduced to the control system through the feedforward loop under practical power grids, leading to a different current loop model from the original one, then conventional LCL filter design for single-current-loop control may be inappropriate. In this paper, the detailed modeling of current control loop with unit PCC voltage feedforward is presented. Based on the established model, it is found that unstable open-loop poles may appear under grid impedance variation, which thus may cause system instability. Therefore, the robust design regions of LCL filters against grid impedance variation are proposed for single-current-loop control schemes. Moreover, another interesting finding is that the feedforward control can help maintain a high current control bandwidth under grid impedance variation. This feature is highly desirable if multiple resonant controllers are employed for harmonic compensation. Experimental results are finally presented to verify the theoretical analysis and robust design presented in this paper.